Research on intelligent indoor location method based on Wi-Fi fingerprint. (24th February 2021) - Yuan, Jie; He, Yi
In order to improve indoor location performance based on Wi-Fi fingerprint, the novel algorithm is put forward based on K-mean algorithm and fuzzy support vector machine. Firstly, the basic theories of Wi-Fi location technology, indoor location principle based on location fingerprint database are studied. Secondly, the basic theories of K-means algorithm, fuzzy support vector machine and nearest incremental algorithm are discussed, and the corresponding mathematical model is deduced. Third, the Wi-Fi fingerprint location algorithm procedure is designed. Finally, the simulation analysis is carried out, and results show that the proposed method has higher location performance.